THE ROLE OF INDONESIAN POLICE INTELLIGENCE IN PREVENTING MASS SOCCER SPECTATORS’ RIOT BASED ON THE REGULATION OF THE HEAD OF SECURITY INTELLIGENCE AGENCY OF INDONESIAN NATIONAL POLICE NO. 2/2013 - Putra, Milenio Januar; Setiasih, Herma (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The Kanjuruhan tragedy in Malang between Arema Malang and Persebaya Surabaya soccer supporters led to unexpected clashes due to disappointment from the locals’ defeat, and it caused many casualties. Therefore, this research is conducted to find out and analyze the role of Indonesian National Police intelligence in securing football that has clashed and caused casualties at Kanjuruhan Malang stadium based on Regulation of the Head of Security Intelligence Agency of Indonesian National Police No. 2/2013 on Security Intelligence of Indonesian National Police. This research is a normative legal research combined with juridical type. The problem approach used is a statutory approach, concept approach, and case approach. In addition, legal source data consist of 3 sources, such as primary, secondary, and tersier. The findings of this research indicated that using tear gas in the Kanjuruhan riot is actually regulated in the National Police Chief Regulation No. 1/2009 on the use of force in police actions. However, this violates the rules of FIFA as the federation that oversees world football. Furthermore, the role of police intelligence in securing football matches at Kanjuruhan Malang is conducted with targeted activities through the preparation stage, implementation stage, and termination stage.